The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1002/j.1556-6978.2012.00004.x
|View full text |Cite
|
Sign up to set email alerts
|

Preparing School Counselors to Promote Academic Development

Abstract: Reform in school counseling over the last decade has focused on how school counselors can contribute to the academic development of K–12 students. Consensus in this matter has yet to be achieved, and recommendations about how best to prepare preservice K–12 school counselors for this objective have been incomplete. The authors describe content and supervised experiences from a preservice course designed to prepare school counselors to promote student academic development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The findings consistently showed that the demographic variables and pretest scores specified in the models did not explain a considerable amount of the variance in the posttest scores that was due to individual differences across students (ranging from 20% to 97%). The findings also supported previous research that highlighted the potential efficacy of classroom guidance efforts by school counselors (Galassi & Akos, ; Schellenberg & Grothaus, ; Whiston et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings consistently showed that the demographic variables and pretest scores specified in the models did not explain a considerable amount of the variance in the posttest scores that was due to individual differences across students (ranging from 20% to 97%). The findings also supported previous research that highlighted the potential efficacy of classroom guidance efforts by school counselors (Galassi & Akos, ; Schellenberg & Grothaus, ; Whiston et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In their review of school counseling outcome research, Whiston, Tai, Rahardja, and Eder (2011) concluded that proactive curriculum interventions delivered by school counselors improved student outcomes. For example, classroom guidance enhanced academic development (Galassi & Akos, 2012) and improved the behavior of student participants (Schellenberg & Grothaus, 2011). This study evaluated the efficacy of a classroom guidance curriculum.…”
Section: Purpose Of the Studymentioning
confidence: 99%
“…As a result, teachers have increased opportunities to spot aberrant behavior patterns, suicide warning signs, or mental health concerns. Galassi and Akos (2014) suggested that school counselors collaborate with other educational stakeholders (e.g., teachers, teachers’ aides, paraprofessionals) to create an environment that promotes student success. In a similar manner, a school counselor who lacks stakeholder support for a school-wide suicide prevention program will struggle to succeed.…”
Section: Steps For Building a School Prevention Programmentioning
confidence: 99%
“…The world goes through cultural, technological, and educational changes and developments, since the beginning of the 21st century, which affects all aspects of life, such as economical, social, educational, especially the university education, therefore the importance of identifying vocational and psychological guiding and counseling needs arose for the University students, as an urgent need to help universities' students face the challenges that posed by the educational quality and labor market requirements (Rida, 2006;Al-Dulaim, 2011), where the University mainly; participate in building the student personality through providing advance and developed curriculums, and by providing the human relations and social interactions, while the student personality develops and shows during the University preparation level of achievement and ambition, and satisfy the basic needs of individuals, not to mention that current culture and evolution circumstances plays a large role in satisfying the individual needs, therefore the non-developed societies cares continuously about satisfying the physiological and security needs more than satisfying the other needs of its members, while the developed societies cares about satisfying the self-actualization needs (Galassi & Akos, 2012), and Maslow sees that distress and frustration about dissatisfaction of the need is the main factor in the personality growth lack of integration, and is also the main reason for the occurrence of abnormalities or defects types in the formation of individual personality through his life (Al-Swailem, 2002& Morsi, 1997.…”
Section: Introductionmentioning
confidence: 99%